Assessment of upscaling potential of alternative adsorbent materials for highway stormwater treatment in cold climates. Issue 6 (19th March 2017) - Ilyas, Aamir; Muthanna, Tone M.
ABSTRACT: Generally, studies on alternative adsorbents focus on adsorbent removal capacity, as a function of pollutant concentration, and other practical aspects, such as costs, environmental impact and end of life costs, that can affect the upscaling of adsorbents for real-life applications, are not explicitly considered. Therefore, this study combines multi-criteria modeling with experimental evaluation to integrate both technical and non-technical factors in assessing the upscaling potential of alternative adsorbents. The experimental step was used to verify the reported pollutant removal as well as testing environmental stability, of the alternative adsorbents, in cold climates. Important factors/criteria for the upscaling process were identified with the help of principal component analysis. The results indicated that adsorbents such as pine bark, olivine and charcoal were the best available options for upscaling. The statistical analysis revealed that factors such as initial costs, hydraulic loads and end-of-life costs were important for the upscaling process and, therefore, should be explicitly included in any future evaluation of the alternative adsorbents.